Graphene oxide induces apoptotic cell death in endothelial cells by activating autophagy via calcium-dependent phosphorylation of c-Jun N-terminal kinases. (December 2016) - Lim, Mi-Hee; Jeung, In Cheul; Jeong, Jinyoung; Yoon, Sung-Jin; Lee, Sang-Hyun; Park, Jongjin; Kang, Yu-Seon; Lee, Hansu; Park, Young-Jun; Lee, Hee Gu; Lee, Seon-Jin; Han, Baek Soo; et al.
Graphical abstract: Abstract: Despite the rapid expansion of the biomedical applications of graphene oxide (GO), safety issues related to GO, particularly with regard to its effects on vascular endothelial cells (ECs), have been poorly evaluated. To explore possible GO-mediated vasculature cytotoxicity and determine lateral GO size relevance, we constructed four types of GO: micrometer-sized GO (MGO; 1089.9 ± 135.3 nm), submicrometer-sized GO (SGO; 390.2 ± 51.4 nm), nanometer-sized GO (NGO; 65.5 ± 16.3 nm), and graphene quantum dots (GQDs). All types but GQD showed a significant decrease in cellular viability in a dose-dependent manner. Notably, SGO or NGO, but not MGO, potently induced apoptosis while causing no detectable necrosis. Subsequently, SGO or NGO markedly induced autophagy through a process dependent on the c-Jun N-terminal kinase (JNK)-mediated phosphorylation of B-cell lymphoma 2 (Bcl-2), leading to the dissociation of Beclin-1 from the Beclin-1–Bcl-2 complex. Autophagy suppression attenuated the SGO- or NGO-induced apoptotic cell death of ECs, suggesting that SGO- or NGO-induced cytotoxicity is associated with autophagy. Moreover, SGO or NGO significantly induced increased intracellular calcium ion (Ca 2+ ) levels. Intracellular Ca 2+ chelation with BAPTA-AM significantly attenuated microtubule-associated protein 1A/1B-light chain 3-II accumulation and JNK phosphorylation, resulting in reduced autophagy. Furthermore, we found that SGO or NGO induced Ca 2+ release from the endoplasmic reticulum through the PLC β3/IP3 /IP3 R signaling axis. These results elucidate the mechanism underlying the size-dependent cytotoxicity of GOs in the vasculature and may facilitate the development of a safer biomedical application of GOs. Statement of Significance: Graphene oxide (GO) have received considerable attention with respect to their utilization in biomedical applications. However, GO-related safety issues concerning human vasculature are very limited. In this manuscript, we report for the first time the differential size-related biological effects of GOs on endothelial cells (ECs). Notably, Subnanometer- and nanometersized GOs induce apoptotic death in ECs via autophagy activation. We propose a molecular mechanism for the GO-induced autophagic cell death through the PLCβ3/IP3/Ca 2+ /JNK signaling axis. Our findings could be provide a better understanding of the GO sizedependent cytotoxicity in vasculature and facilitate the future development of safer biomedical applications of GOs.